Severe hypoxic exercise does not impair lung diffusion in elite swimmers - García, I.; Drobnic, F.; Javierre, C.; Pons, V.; Viscor, G. (High Altitude Medicine & Biology, 2021)
Background: Exercise performed at high altitude may cause a subclinical pulmonary interstitial edema that can worsen gas exchange function. This study aimed to evaluate whether there are changes in alveolar-capillary diffusion after exercise during a short-term exposure to hypobaric hypoxia in elite swimmers.